Effects of phosphorus addition on nitrogen cycle and fluxes of N2O and CH4 in tropical tree plantation soils in Thailand - Mori, Taiki; Wachrinrat, Chongrak; Staporn, Duriya; Meunpong, Ponthep; Suebsai, Warawich; Matsubara, Kazuki; Boonsri, Khitja; Lumban, Warisa; Kuawong, Manassawee; Phukdee, Thanida; Srifai, Juruwan; Boonman, Kannika (Agriculture and Natural Resources, 2017)
An incubation experiment was conducted to test the effects of phosphorus (P) addition on nitrous oxide (N2O) emissions and methane (CH4) uptakes, using tropical tree plantation soils in Thailand. Soil samples were taken from five forest stands-Acacia auriculiformis, Acacia mangium, Eucalyptus camaldulensis, Hopea odorata, and Xylia xylocarpadan-incubated at 80% water holding capacity. P addition stimulated N2O emissions only in Xylia xylocarpa soils. Since P addition tended to increase net ammonification rates in Xylia xylocarpa soils, the stimulated N2O emissions were suggested to be due to the stimulated nitrogen (N) cycle by P addition and the higher N supply for nitrification and denitrification. In other soils, P addition had no effects on N2O emissions or soil N properties, except that P addition tended to increase the soil microbial biomass N in Acacia auriculiformis soils. No effects of P addition were observed on CH4 uptakes in any soil. It is suggested that P addition on N2O and CH4 fluxes at the study site were not significant, at least under laboratory conditions.